2017
DOI: 10.1113/jp274119
|View full text |Cite|
|
Sign up to set email alerts
|

Convergent ERK1/2, p38 and JNK mitogen activated protein kinases (MAPKs) signalling mediate catecholoestradiol‐induced proliferation of ovine uterine artery endothelial cells

Abstract: Previously we demonstrated that the biologically active metabolites of 17β-oestradiol, 2-hydroxyoestradiol (2-OHE ) and 4-hydroxyoestradiol (4-OHE ), stimulate pregnancy-specific proliferation of uterine artery endothelial cells derived from pregnant (P-UAECs), but not non-pregnant ewes. However, unlike 17β-oestradiol, which induces proliferation via oestrogen receptor-β (ER-β), the catecholoestradiols mediate P-UAEC proliferation via β-adrenoceptors (β-AR) and independently of classic oestrogen receptors. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…in this issue of The Journal of Physiology demonstrates that E2β, 2‐hydroxyoestradiol, 4‐hydroxyoestradiol, norepinephrine, and epinephrine stimulate proliferation of uterine artery endothelial cells via activation of three convergent MAPK pathways (ERK1/2, p38 and JNK) (Landeros et al . ). The observations in the present and previous studies from the Magness laboratory are interesting.…”
Section: Overview Of Signalling Pathways In Uterine Artery Endotheliamentioning
confidence: 97%
“…in this issue of The Journal of Physiology demonstrates that E2β, 2‐hydroxyoestradiol, 4‐hydroxyoestradiol, norepinephrine, and epinephrine stimulate proliferation of uterine artery endothelial cells via activation of three convergent MAPK pathways (ERK1/2, p38 and JNK) (Landeros et al . ). The observations in the present and previous studies from the Magness laboratory are interesting.…”
Section: Overview Of Signalling Pathways In Uterine Artery Endotheliamentioning
confidence: 97%
“…Noteworthy, the mode of p42/44 MAPK activation by THC was found to be biphasic which is in line with cannabinoid-induced p42/44 MAPK activation in neuroglioma cells [ 28 ]. In the latter study, the endocannabinoid analogue R(+)-methanandamide was shown to confer an early peak after 15 min and a delayed peak after 4 and 8 h. Similar biphasic p42/44 MAPK activations were reported for doxorubicin in neuronal cells [ 29 ], for catechol metabolites of 17β-estradiol in pregnancy-derived ovine uterine artery endothelial cells [ 30 ] and uridine 5´-triphosphate-treated Schwannoma cells [ 31 ]. In the latter investigation biphasic p42/44 MAPK regulation was likewise associated with increased cellular migration [ 31 ].…”
Section: Discussionmentioning
confidence: 63%
“…All procedures were approved by the University of Wisconsin-Madison Research Animal Care and Use Committees for both the Medical School and the College of Agricultural and Life Sciences, following the recommendation from the American Veterinary Medicine Association guidelines for humane treatment and euthanasia of laboratory farm animals as described by Landeros et al 41 Briefly, UAECs were obtained from P ewes (gestational age ¼ 120-130; term ¼ 147 days) or luteal phase NP ewes of mixed Western and Polypay breeds and euthanized under sodium pentobarbital (50-70 mg/kg) anesthesia through bilateral thoracotomy and exsanguination by cardiac laceration. Uterine artery endothelial cells were isolated from both left and right uterine arteries by collagenase digestion and cultured in growth media, endothelial basal media (EBM), with 20% fetal bovine serum, 100 mg/mL penicillin, and 100 mg/mL streptomycin.…”
Section: Cell Preparation and Culturementioning
confidence: 99%